2015
DOI: 10.1037/hea0000098
|View full text |Cite|
|
Sign up to set email alerts
|

A social rank explanation of how money influences health.

Abstract: Objective: Financial resources are a potent determinant of health, yet it remains unclear why this is the case. We aimed to identify whether the frequently observed association between absolute levels of monetary resources and health may occur because money acts an indirect proxy for a person’s social rank. Method: To address this question we examined over 230,000 observations on 40,400 adults drawn from two representative national panel studies; the British Household Panel Survey and the English Longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 40 publications
7
63
0
Order By: Relevance
“…The inclusion of income rank largely eliminated the relationship between absolute income and suicidality in the statistical models, indicating that it is income rank rather than income per se that accounts for the income-suicidality relationship. This is consistent with previous findings showing that the income rank variable within similar social comparison groups accounts for the associations between absolute income and life satisfaction [30], distress [31], and health [32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The inclusion of income rank largely eliminated the relationship between absolute income and suicidality in the statistical models, indicating that it is income rank rather than income per se that accounts for the income-suicidality relationship. This is consistent with previous findings showing that the income rank variable within similar social comparison groups accounts for the associations between absolute income and life satisfaction [30], distress [31], and health [32].…”
Section: Discussionsupporting
confidence: 82%
“…This finding has received further support from Wood and colleagues [31] who found that the income rank variable wholly accounted for the relationship between income and mental distress. The psychosocial explanation of the effect of income upon health has also been strengthened by a recent study [32] where income rank explained the relationship between income/wealth and a number of health outcomes including physical functioning, obesity and long standing illness. The study authors concluded that social position rather than material conditions may account for the impact of money on health [32].…”
Section: How Are Social Comparisons Related To Suicidal Outcomes?mentioning
confidence: 99%
“…Moreover, associations between income rank and allostatic load strengthen the pathway between rank, stress and psychological distress, strongly suggesting that income rank relates to health (Daly, Boyce and Wood, 2015). These studies do however have methodological limitations: suicidal thoughts and attempts were restricted to cross-sectional analyses (Wetherall et al, 2015) and the longitudinal analyses (Wood, Boyce, et al, 2012;Hounkpatin et al, 2015) did not control for unobserved variance, introducing the possibility that unobserved variance influenced their results.…”
Section: Characteristics Of Income and Status Comparisonsmentioning
confidence: 99%
“…This is standard practice and approximates spending power (Wood, Boyce, et al, 2012;Daly, Boyce and Wood, 2015;Wetherall et al, 2015). Absolute income was log transformed to reduce skew, then normalised between 0 and 1.…”
Section: Absolute Incomementioning
confidence: 99%
“…Prior research on racial and health inequalities, for example, has documented the physiological impact of social denigration; such stress can activate the PERCEIVED WEIGHT AND HEALTH 5 sympathetic nervous system and induce sustained neuroendorcrine responses with potential deleterious health consequences (Daly, Boyce, & Wood, 2015;Williams & Mohammed, 2009). Similarly, weight discrimination could mobilize the fight-or-flight response that is adaptive in times of acute physical threat but maladaptive if chronically activated in response to social threat.…”
Section: Perceived Weight and Healthmentioning
confidence: 99%